MENUMBUHKEMBANGKAN MINAT BACA MENUJU MASYARAKAT LITERAT - Wahyuni, Sri (Diksi, 2015)
Research findings show that in general Indonesian students' reading ability is still low. This is attributable to, among others, poor reading habit, which is caused by low reading motivation. Several aspects cause low reading motivation: (1) family and neighborhood environments that do not support reading habit, (2) society's low bookbuying power, (3) limited number of good libraries, (4) negative effects of electronic media development, (5) learning model that in general does not make students read, and (6) inappropriate learning system for reading. To improve reading motivation several attempts can be made: (1) making children get used to reading since their early age, (2) providing interesting books, (3) creating an environment conducive for reading, (4) reconstructing the library performance to make it interesting, and (5) developing a learning model for reading that is enjoyable, varied, and educative. Keywords: reading motivation, literate society